Nutrient Levels in Brassicaceae Microgreens Increase Under Tailored Light-Emitting Diode Spectra - Samuolienė, Giedre; Brazaitytė, Aušra; Viršilė, Akvile; Miliauskienė, Jurga; Vaštakaitė-Kairienė, Viktorija; Duchovskis, Pavelas (Frontiers in Plant Science, 2019)
To increase the nutritional value and levels of essential minerals in vegetable food, microgreens are promising targets. The metabolic processes of microgreens can be managed with different cultivation techniques, which include manipulating the properties of light derived by light-emitting diodes (LEDs). In this study Brassicaceae microgreens (kohlrabi Brassica oleracea var. gongylodes, broccoli Brassica oleracea and mizuna Brassica rapa var. Japonica) were cultivated under different light spectral quality, and the metabolic changes insoluble sugars (hexoses and sucrose), ascorbic acid, β-carotene, and contents of non-heme iron (Fe) and its connection with magnesium (Mg) or calcium (Ca) levels were monitored. Plants grew under the primary LED light spectrum (the combination of blue light at 447 nm, red at 638 and 665 nm and far-red at 731 nm) or supplemented with LED green light at 520 nm, yellow at 595 nm, or orange at 622 nm. The photoperiod was16 h, and a total PPFD of 300 µmol m-2 s-1 was maintained. Under supplemental yellow light at 595 nm, the content of soluble carbohydrates increased significantly in mizuna and broccoli. Under all supplemental light components, β-carotene accumulated in mizuna, and ascorbic acid accumulated significantly in kohlrabi. Under supplemental orange light at 622 nm, Fe, Mg, and Ca contents increased significantly in all microgreens. The accumulation of Fe was highly dependent on promoters and inhibitors of Fe absorption, as demonstrated by the very strong positive correlations between Fe and Ca and between Fe and Mg in kohlrabi and broccoli, and the strong negative correlations between Fe and β-carotene and between Fe and soluble carbohydrates in kohlrabi. Thus, the metabolic changes that occurred in treated microgreens led to increases in the contents of essential nutrients. Therefore, selected supplemental LED wavelengths can be used in the cultivation of Brassicaceae microgreens to preserve and increase the contents of specific nutritionally valuable metabolites.